The routine use of evaluation by art therapists and allied health professionals in everyday clinical practice. Issue 1 (2nd January 2016) - Chenery, T.; Fulton, J.; Mellor-Clark, J.; Mellor-Clark, S.; Willoughby-Booth, S. N.
ABSTRACT: This article outlines a pilot project to support the use of the Clinical Outcomes in Routine Evaluation (CORE) System by arts therapists 1 and other Allied Health Professionals (AHPs) and the establishment of a Practice Research Network (PRN) to evaluate the use of the system in routine clinical practice. It describes the aims of the project, the establishment of the PRN, the data collected during the project and its impact on the practitioners involved. It draws initial conclusions from the project and discusses the strengths and limitations of this approach to measuring the outcomes of psychological therapy.